Droplet dispersion simulation to evaluate airborne virus infection risk in outdoor sports stadiums - Sangwon KIM; Junya ONISHI; Rahul BALE; Makoto TSUBOKURA (Journal of Fluid Science and Technology, 2024)
In this study, the dispersion of droplets and the associated risk of airborne disease transmission are investigated under various seating arrangements and airflow conditions, encompassing both flat and inclined settings. The numerical framework known as “CUBE” integrates a fully compressible Navier–Stokes solver with a Lagrangian droplet dynamics model, thus facilitating large-scale parallel simulations. This framework employs a building-cube method-based meshing to model the Eulerian mesh, with the same number of cells decomposed in each cube unit. It also disaggregates the Lagrangian marker particle data within each cube unit, thus increasing the parallel computing efficiency. The simulation results reveal that both droplet dispersion patterns and infection risk are substantially influenced by the seating layout and direction of the wind. Notably, wind coming from an angle of 90° significantly reduces both localized droplet dispersion and overall infection risk compared with that from an angle of 0°. Therefore, strategic seating configurations effectively mitigate infection risk under various environmental and airflow conditions. This knowledge is vital for designing public domains to curb the transmission of airborne illnesses such as COVID-19.